Global redistribution of income and household energy footprints: a computational thought experiment - Y. Oswald; J.K. Steinberger; D. Ivanova; J. Millward-Hopkins (Global Sustainability, 2021)
Non-technical summary Global income inequality and energy consumption inequality are related. High-income households consume more energy than low-income ones, and for different purposes. Here, we explore the global household energy consumption implications of global income redistribution. We show that global income inequality shapes not only inequalities of energy consumption but the quantity and composition of overall energy demand. Our results call for the inclusion of income distribution into energy system models, as well as into energy and climate policy.